FACTORS RELATING TO THE IMPLEMENTATION OF THE INTEGRATED MANAGEMENT PROGRAM FOR TODDLER SICKNESS (MTBS) AT KOPELMA DARUSSALAM HEALTH CENTER SYIAH KUALA DISTRICT, BANDA ACEH CITY - Raiyan, Deka; Akbar, Fahrisal; Anwar, Syarifuddin; Ramadhana, Phossy Vionica (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: The low coverage of IMCI in Aceh is due to the fact that many Puskesmas do not implement the IMCI program. The purpose of this study was to determine the factors associated with the implementation of the IMCI program at the Kopelma Darussalam Health Center, Syiah Kuala District, Banda Aceh City in 2019. Methods: This research is descriptive analytic with cross sectional design. The population in this study were all respondents who brought children under five to the CFR clinic of Kopelma Darussalam Health Center. The sample size was 46 respondents, the sampling technique in this study was accidental sampling. Results: the results of this study indicate that from the bivariate analysis using the chi square test shows that there is a relationship between the role of health workers (p-value=0.001), affordability (p-value=0.019), maternal counseling (p-value=0.003) with the implementation of the IMCI program. Suggestion: It is expected that the Head of Kopelma Darussalam Health Center will try to improve the performance of MTBS program implementers, adding health workers trained in MTBS. Mothers are expected to follow all the procedures for integrated management of sick toddlers in children in caring for children.